THE UTILIZATION OF GOOGLE CLASSROOM AS E-LEARNING MEDIA OF ENGLISH FOR EFL STUDENTS AT VOCATIONAL HIGH SCHOOOL - Cucum Rohmawati; Dede Rohadi Fajri (Journal of English Language Teaching and Literature (JELTL), 2022)
Based on the preliminary survey, it is known that SMKN 3 Kota Serang has tried to have e-learning to support online teaching and learning activities, so teachers and students will be able to do online learning in the pandemic of covid-19.A qualitative approach is used in conducting this research because it describes the Utilization of Google Classroom as E-Learning for conducting the English teaching-learning process during pandemic Covid-19. The case study was chosen as the research method in this study. From the result in figure 1, it can be seen that most respondents were enthusiastic during the English teaching-learning process through Google Classroom. Based on the post-survey, most respondents could understand the use of all the main features of Google Classroom, such as creating a new class, subject lesson, assignment, quiz, question, grading assignment and quiz, posting announcement for their students, etc. From all explanations of the utilization of Google Classroom for teaching English in SMKN 3 Kota Serang, it can be seen that a positive result was gotten. It is also supported by the result of a survey about students’ perception of English learning through the utilization of Google Classroom. Students’ Feedback of Utilization Google Classroom as E-learning Media of English. From the result in figure 1, it can be seen that most respondents were enthusiastic during the English teaching-learning process through Google Classroom.